2021
DOI: 10.1007/s11257-021-09300-z
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between user types and gamification designs

Abstract: Gamification has been discussed as a standout approach to improve user experience, with different studies showing that users can have different preferences over game elements according to their user types. However, relatively less is known how different kinds of users may react to different types of gamification. Therefore, in this study ($$N=331$$ N = 331 ) we investigate how user orientation (Achiever, Disru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 52 publications
3
31
0
5
Order By: Relevance
“…However, the elderly population has inconsistent preferences for gamification elements due to their age span and individual differences in background. Studies have shown that some gamification designs using a "one-size-fits-all" strategy do not improve user satisfaction because these designs ignore user differences [28] and user preferences [29,30]. Therefore, to design gamified applications for older people, it is necessary to study their preferences to make the products more attractive and usable, and to better motivate users to achieve their goals [31].…”
Section: Related Workmentioning
confidence: 99%
“…However, the elderly population has inconsistent preferences for gamification elements due to their age span and individual differences in background. Studies have shown that some gamification designs using a "one-size-fits-all" strategy do not improve user satisfaction because these designs ignore user differences [28] and user preferences [29,30]. Therefore, to design gamified applications for older people, it is necessary to study their preferences to make the products more attractive and usable, and to better motivate users to achieve their goals [31].…”
Section: Related Workmentioning
confidence: 99%
“…When investigating aspects of human behaviour, there is a long-standing tradition of using games and scenarios that rely on a narrative in order to engage participants. The idea is that such tools will elicit more realistic responses than questionnaires -this idea was refined in [54] by associating user types with particular game designs.…”
Section: Related Researchmentioning
confidence: 99%
“…A gamificação baseada em performance, assim como os demais designs mencionados anteriormente, é um tipo de personalização da gamificação, o qual possui elementos associados à resposta do ambiente, podendo estes serem utilizados para fornecer feedback ao estudante (Santos et al, 2021). O ponto é a unidade usada para medir o desempenho dos usuários.…”
Section: Gamificação Baseada Em Performanceunclassified
“…Mais recentemente, Santos et al (2021) realizou um estudo com o objetivo de responder como os perfis de usuários estão associados com a preferência e o senso percebido de realização em diferentes designs de gamificação. O estudo foi dividido em cinco fases, sendo elas: o desenho de storyboards, desenho da pesquisa, estudo piloto, aplicação de pesquisa e análise de dados, e analisou 331 respostas válidas e voluntárias, obtidas através da divulgação da pesquisa pelas redes sociais e e-mail durante um período de 38 dias.…”
Section: Trabalhos Relacionadosunclassified
See 1 more Smart Citation